Case Report: Importance of B-scan Ultrasonography for the Detection of Choroidal Melanoma. Issue 10 (October 2018) - Wilczek, Margaret A.; Gold, Aaron S.; Ehlies, Fiona J.; Murray, Timothy G.
Abstract : SIGNIFICANCE: This case highlights the importance of using ultrasonography to evaluate an eye that has no clear view of the fundus. PURPOSE: Uveal melanoma stems from melanocytes found in the iris, ciliary body, and choroid, and it is the most common primary intraocular malignancy found in adults. The lesion is identified predominantly via fundus biomicroscopy and binocular indirect ophthalmoscopy. The authors present a unique case where visual evaluation of the fundus was not possible, and ultrasonography was used to assess the retina and choroid. CASE REPORT: A 38-year-old Hispanic man with prior ocular trauma presented with an eye that could not be clinically examined owing to complete pupil occlusion. The diagnosis of presumed uveal melanoma was made exclusively based on the outcome of ocular ultrasonography. Further histologic, antibody, and genetic testing was completed once the patient had undergone treatment of the affected eye and uveal melanoma was confirmed. CONCLUSIONS: In this rare instance, B-scan ultrasonography provided a finding that required the patient to undergo enucleation in an eye without visual potential. Genetic testing was then used to appropriately categorize the tumor as a class 1B melanoma, indicating that there is a risk of metastasis. Consequently, the patient is being monitored by a medical oncologist.